Performance Measures in Binary Classification - Kohl, Matthias (International Journal of Statistics in Medical Research, 2012)
We give a brief overview over common performance measures for binary classification. We cover sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio as well as ROC curve and AUC.